Desarrollo de una prótesis transradial externa para miembro superior basada en impresión 3D (2020)
Urrently 3D printing is contributing greatly to the manufacture of prostheses. Its use can reduce the cost of prosthetic fabrication and allows the sea to be more accessible to those who need it. 3D printing allows us to make designs that fit better to the needs of each patient, through 3D printing can replace the body image and simulate the movements of the hands mechanically, it is also possible to develop prototypes in which Electronic components can be implemented to achieve an electromechanical prosthesis.Currently being developed a prototype external transradial prosthesis for a superior limb is based on 3D printing that fits the needs of the patient, this prosthesis has been adapted to the normal movements of the hands of the mechanical form. Several designs will be made in order to see the prototypes according to the needs and desires of the user. Through 3D printing we can manufacture prostheses that are modular, lightweight and comfortable enough, as well as low cost and manufacturing time. 3D printing is a technology that is advancing more and more and this is a more suitable solution for people who have a higher or lower type of disability